Atorvastatin inhibits pyroptosis through the lncRNA NEXN-AS1/NEXN pathway in human vascular endothelial cells. (January 2020) - Wu, Li-Mei; Wu, Shao-Guo; Chen, Fei; Wu, Qian; Wu, Chang-Meng; Kang, Chun-Min; He, Xin; Zhang, Ru-Yi; Lu, Zhi-Feng; Li, Xue-Heng; Xu, Yuan-Jun; Li, Li-Min; et al.
Abstract: Background and aims: Many clinical trials have demonstrated that statins convey protective effects against atherosclerosis independent of cholesterol-lowering capacities. Other evidence indicates that pyroptosis, a type of programmed cell death, is likely involved in atherosclerosis, but the effects and mechanisms of statins on pyroptosis must be further revealed. Methods: Here, we explored the effects and mechanisms of atorvastatin on pyroptosis in human vascular endothelial cells by quantitative real-time polymerase chain reaction and Western blot analyses. Results: Atorvastatin upregulated long non-coding RNA (lncRNA) NEXN-AS1 and the expression of NEXN at both the mRNA and protein levels in a concentration- and time-dependent manner. Atorvastatin inhibited pyroptosis by decreasing the expression levels of the canonical inflammasome pathway biomarkers NLRP3, caspase-1, GSDMD, IL-1β, and IL-18 at both the mRNA and protein levels. The promotion effects of atorvastatin on NEXN-AS1 and NEXN expression could be significantly abolished by knockdown of lncRNA NEXN-AS1 or NEXN, and its inhibitory effects on pyroptosis were also markedly offset by knock-down of lncRNA NEXN-AS1 or interference of NEXN . Conclusions: These results demonstrated that atorvastatin regulated pyroptosis via the lncRNA NEXN-AS1-NEXN pathway, which provides a new insight into the mechanism of how atorvastatin promotes non-lipid-lower effects against the development of atherosclerosis and gives new directions on how to reverse atherosclerosis. Graphical abstract: Image 1 Highlights: Atorvastatin upregulates lncRNA NEXN-AS1 and NEXN in EC. Atorvastatin inhibits the canonical inflammasome pathway biomarkers of pyroptosis. Both the above effects can be abolished by knockdown of lncRNA NEXN-AS1 or NEXN.